Value stream analysis of a waste picker cooperative: an approach based on sustainability and lean philosophy - Silva, Marina Guimarães Moreira da; Bouzon, Marina; Silva, Jailson dos Santos (Brazilian Journal of Operations & Production Management, 2023)
Purpose: This article aims to propose improvements to a solid waste cooperative’s value stream from social, environmental, and economic aspects of sustainability and within the scope of lean philosophy. Design/Methodology/Approach: An empirical piece of research was developed to obtain an overview of the productive process of a cooperative located in the city of Florianópolis, in Southern Brazil, starting with the application of Value Stream Mapping (VSM) in a case study. Results: Some sustainability challenges in waste management were identified in the studied cooperative’s reality, such as: Urban Solid Waste (USW) inefficient management; lack of resources to help with basic expenses, which jeopardizes the individual income earned by pickers; risks to workers when carrying out activities without personal protective equipment and instructions on how to perform tasks properly, in addition to the disorganized environment, which results in high piles of waste and puts the workers’ health at risk. Research Limitations: As limitations, it is possible to list the focus on a single material flow for better applicability of VSM and non-implementation of the improvements proposed. Practical Implications: Results contributed to the cooperative analyzed in this study by identifying the main waste that compromise the organization’s operational and sustainable efficiency. Originality/Value: There is a research gap on the thematic axes of this study in the context of waste picker cooperatives; this article is therefore original for addressing the application of VSM with a sustainable bias in reverse logistics of solid waste.